Measuring of Specific Bone Alkaline phosphatase ( BAP ) Bone Remodeling biomarker for Post-COVID Iraqi Patient - Alazawi, Islam S.; Mohammed , Nawar S.; Jassim, Nizar A. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: There are several diseases in the body following recovery from COVID-19 infection because this virus operates on human genes in various types of peripheral tissue in the human body. It penetrates host cells via Angiotensin-converting enzyme-2 receptors and may have effects on bone remodeling, leading to osteopenia or osteoporosis, which are characterized by low bone mineral density, resulting in diminished bone strength. Bone Alkaline Phpsphatase is an enzyme released into the bloodstream as a soluble homodimer after being cleaved by a phospholipase and can be utilized as a biomarker of bone development.Objective: This research was designed to investigate the alteration of bone homeostasis balance in Iraqi post-COVID-19 infection patients.Cases and Methods: This is a case control study. The study has received approval from the ethical committee at the Faculty of Medicine, Baghdad University, established on November 20, 2021–March 2, 2022. A hundred and thirty individuals were enrolled in this study. The subjects were divided into two groups; the first group (80) post-COVID-19 infection patients and the second group (50) non-COVID-19 individuals. Also, measuring markers like serum Angiotensin-converting enzyme-2 and Bone Alkaline Phosphatase by using the ELISA technique. The bone mineral density was measured by a DEXA scan.Results:This study found that there is an effect of coronavirus infection on the bone strength measured by the mean ± SD Bone Alkaline Phosphatase level, which was found to be highly significant in the serum of post-COVID-19 patients when compared with non-COVID-19 individuals (P-value = 0.001), but the mean ± SD of Angiotensin-converting enzyme-2 level was statistically non-significant between the two groups (P-value = 0.13). who had recovered from a coronavirus infection for 3 months or more. Also, the bone mineral density of Post COVID-19 patients that was measured by DEXA scan had a highly significant T-score% when compared between the two groups.Conclusions:This research found that COVID-19 has an impact on the bone remodeling process, leading to osteopenia or osteoporosis, which may be identified by checking the blood levels of the bone biomarker BAP and the bone mineral density (by DEXA scan) at least three months following coronavirus recovery. This investigation also discovered that some of the individuals had osteopenia rather than osteoporosis.